A Textbook of Advanced Oral and Maxillofacial Surgery - Hosein Kalantar Motamedi, Mohammad (IntechOpen, 2013)
The discipline of oral and maxillofacial surgery covers a wide range of diseases, conditions, injuries and defects of the head, neck, face and jaws as well as the hard and soft tissues of the oral cavity. It is an internationally recognized surgical specialty rapidly changing with evolving advancements in technology. Specialists of this field care for patients with problems such as impacted teeth, facial pain, misaligned jaws, facial injuries, oral cancer, cysts, tumors, and patients requiring facial cosmetic surgery and dental implants. New texts are needed to keep practitioners up-to-date because advancements are being made world-wide on a daily basis. This book seeks to present advanced concepts on complex topics within the scope of this dynamic discipline.